2003
DOI: 10.1515/bc.2003.013
|View full text |Cite
|
Sign up to set email alerts
|

The PPIase Active Site of Legionella pneumophila Mip Protein Is Involved in the Infection of Eukaryotic Host Cells

Abstract: We analysed eight monoclonal antibodies (mAbs) directed against the Mip (macrophage infectivity potentiator) protein, a virulence factor of the intracellular pathogen Legionella pneumophila. Mip belongs to the FK506-binding proteins (FKBPs) and exhibits peptidyl prolyl cis/trans isomerase (PPIase) activity. Five of the mAbs recognised epitopes in the C-terminal, FKBP-homologous domain of Mip, which is highly conserved among all Legionella species. Upon immunological binding to Mip, all but one of these mAbs ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
2

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 52 publications
0
22
0
2
Order By: Relevance
“…However, subsequent work on a parvulinlike PPIase indicated that vanishingly low levels of enzyme activity might suffice to ensure protection against loss of PPIase function (16). Consequently, targeting the PPIase domain of L. pneumophila Mip with activity-neutralizing monoclonal antibodies inhibited Legionella infection of cells, and FK506 or rapamycin inhibited transmigration of L. pneumophila across NCl-H292 lung epithelial cells (19,42). In addition, removal of the PPIase domain of L. pneumophila Mip attenuated virulence in guinea pig model of infection (25).…”
Section: Discussionmentioning
confidence: 99%
“…However, subsequent work on a parvulinlike PPIase indicated that vanishingly low levels of enzyme activity might suffice to ensure protection against loss of PPIase function (16). Consequently, targeting the PPIase domain of L. pneumophila Mip with activity-neutralizing monoclonal antibodies inhibited Legionella infection of cells, and FK506 or rapamycin inhibited transmigration of L. pneumophila across NCl-H292 lung epithelial cells (19,42). In addition, removal of the PPIase domain of L. pneumophila Mip attenuated virulence in guinea pig model of infection (25).…”
Section: Discussionmentioning
confidence: 99%
“…L. pneumophila constitutes a broad relatedness group, however, so detection of a representative of the group does not indicate a pathogen. Because of the potential human health implication of this detection, we conducted quantitative PCR (QPCR) assays with a L. pneumophila-specific primer pair that targets a pathogenesis gene, the macrophage infectivity potentiator (mip) gene (20)(21)(22)(23)(24), to screen a subset of samples. Thirty-six samples (16 water and 20 swabs, representing 10 cities) were tested in duplicate reactions, including samples with positive L. pneumophila detection by sequence.…”
Section: Regionmentioning
confidence: 99%
“…Although contradictory evidence has been presented for the requirement of the active enzyme site within the protein for virulence of Legionella (22,33), many of the studies described above clearly demonstrated that expression of microbial MIP (and homologues) appeared to have direct relevance to the survival of important human pathogens that have intracellular stages in their life cycles (20).…”
mentioning
confidence: 99%